Hubungan Antara Durasi Bermain Game Online dengan Interaksi Sosial Teman Sebaya Pada Siswa Di SMA Negeri 18 Kota Bandung - Hotmaida, Linda; Doloksaribu, Juliyanti (JURNAL KESEHATAN KARTIKA, 2021)
Online games are electronic games connected internet which are like by teenagers. Overuse of online games might cause addiction. The negative impact of playing online games has lowered teenagers’ social interactions, it also made teenagers ignorant and uncaring to their environment. This research is aimed to empirically find out the relation between the duration of online gaming and the social interaction with peers of similar age. This research involved 253 students in Bandung City Public High School 18. This research is of a quantitative kind with a cross sectional design. Sample acquirement is done using proportionate stratified random sampling technique. The result of this research showed that the majority of respondents excessively play online games (>3 hours/day) with the number up to 163 respondents (64.4%), and some of the respondents have social interactions in the “high” category, numbering up to 134 people (53.0%). The Chi square statistical test result showed P value = 0.079 > α (0.05) which means that there are no relation between the duration of online gaming with social interactions. High intensity online gaming may lower teenagers’ interaction with the society and surrounding environment. Although an increase in online socialization, at the same time a decrease in socialization in real life is also found. The gamers spend more time socializing online. Anti-social behavior, lack of willingness to blend with the society, family and friends are traits shown by those having addiction to gaming. The importance of giving proper understanding to the teenagers regarding negative impact of online gaming, giving guidance towards positive activities to occupy leisure time, limiting the children’s gaming, as well as limiting the use of gadgets are several actions that can be taken by the schools and parents. Keywords: Gadget, Online Game, Social Interaction